PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MOTOR YAMAHA DI KABUPATEN MOROWALI - Djauhar, Asri; Tovan, Tovan; Suharlian, Suharlian (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2021)
This study aims to determine and analyze the effect partially and simultaneously of the brand image consisting of corporate image, product image, and user image on purchasing decisions for Yamaha Motorcycles in Morowali Regency. This type of research is a quantitative study using 120 respondents who were taken by accidental sampling technique. The data collection used a questionnaire and analyzed using multiple linear regressionThe results of the study found that (1) there was a partially positive and significant influence of corporate image on purchasing decisions, (2) there was a partially positive and significant effect of product image on purchasing decisions, (3) there was a partial positive and significant effect of user image on the decision. purchase, (4) there is a positive and significant effect of corporate image, product image, and user image simultaneously on purchasing decisions for Yamaha Motorbikes in Morowali Regency.